The 3rd International Electronic Conference on Environmental Research and Public Health—Public Health Issues in the C 2021
DOI: 10.3390/ecerph-3-09075
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Distractions While Working from Home on Burnout Complaints and Stress Levels among Office Workers during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has led to a massive switch from working at the office to working from home fulltime to minimize the spread of the virus. One of the main challenges, while working from home, are workspace distractions that might also affect employees' mental health. This study aims to analyze the influence of workspace-and personal characteristics, mediated by workspace distractions at home, on employees' stress and burnout levels. Results indicate a major influence of workspace distractions on stress le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…One possible factor that could help mitigate the negative effects could be an employee's ability to control their work environment. A study by Bergefurt et al (2021) found that the presence of distractions in a remote work environment negatively impacted productivity and contributed to stress and burnout, though it suggested that increased control over these factors could mitigate the impact. By exerting a greater degree of control over one's work environment, workers can manage these inhibiting factors, for example by closing their door, purchasing a standing desk, or finding a suitable computer monitor.…”
Section: Introductionmentioning
confidence: 99%
“…One possible factor that could help mitigate the negative effects could be an employee's ability to control their work environment. A study by Bergefurt et al (2021) found that the presence of distractions in a remote work environment negatively impacted productivity and contributed to stress and burnout, though it suggested that increased control over these factors could mitigate the impact. By exerting a greater degree of control over one's work environment, workers can manage these inhibiting factors, for example by closing their door, purchasing a standing desk, or finding a suitable computer monitor.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that focused on occupational health have only observed aspects that were related to poor privacy fit (different types of interruptions, cf. Leroy et al, 2021 , distractions, Bergefurt et al, 2021 ). These studies indicated negative associations with overall stress ( Bergefurt et al, 2021 , 2022 ; see footnote 1), mood ( Bergefurt et al, 2022 ), dimensions of burnout (incl.…”
Section: Introductionmentioning
confidence: 99%
“… Leroy et al, 2021 , distractions, Bergefurt et al, 2021 ). These studies indicated negative associations with overall stress ( Bergefurt et al, 2021 , 2022 ; see footnote 1), mood ( Bergefurt et al, 2022 ), dimensions of burnout (incl. Emotional fatigue, Bergefurt et al, 2021 ; Leroy et al, 2021 ), and multiple aspects of mental health ( Xiao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations